ClpB affects biofilm formation in methicillin-resistant Staphylococcus aureus - Yang, Miao; Wang, Shuang; Qu, Qianwei; Yang, Hai; Liu, Xin; Peng, Wei; Zhou, Yonghui (Frontiers in Microbiology, 2025)
IntroductionThis study aims to explore the effects of the molecular chaperone ClpB on the biofilm formation and pathogenicity of methicillin-resistant Staphylococcus aureus (MRSA).MethodsThe biological membrane formation was evaluated by constructing a clpB knockout strain (ΔclpB) and a complemented strain (CΔclpB) of USA300 MRSA, followed by crystal violet staining, scanning electron microscopy, confocal laser scanning microscopy, and quantitative analysis of extracellular matrix components. A mouse skin infection model was subsequently employed to assess wound healing, histopathological changes, and the expression levels of inflammatory factors.ResultsThe results showed that compared with the wild strain (WT), the biomass of ΔclpB biofilm was significantly reduced (p < 0.0001), the structure was damaged and the production of extracellular matrix (eDNA, polysaccharides, proteins) decreased. CΔclpB then returned to the WT level. In the in vivo experiments, the ΔclpB infection group had faster wound healing, reduced tissue damage, and decreased expressions of TNF-α and IL-6 at both protein and mRNA levels.ConclusionClpB promotes the formation of MRSA biofilms by regulating extracellular matrix synthesis and host inflammatory responses and is a potential target for anti-biofilm therapy.